Performance Index Analysis of Irrigation Areas Using E-PAKSI Software for Sustainable Maintenance in West Java Region - Assyabill, Bramudya Gusti; Maulana, Rahmat; Mulyono, Heri; Winasis, Akbar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzed the performance of the Seuseupan Irrigation Area in Cirebon Regency using the E-PAKSI application. The research employed a descriptive-qualitative method with both primary and secondary data collection. The results revealed a combined main and tertiary irrigation system performance index of 57.62%, which falls into the underperformance category. Water discharge analysis indicated sufficient supply for the rice-rice cropping pattern across the 1,347-hectare service area. However, institutional aspects and personnel were found to be non-compliant with regulations. Furthermore, there was a significant increase in maintenance costs (AKNOP), rising from Rp2.31 billion in 2022 to Rp22.33 billion in 2024. This highlights the critical need for serious attention to the management of irrigation assets and infrastructure in the region.